PENGARUH PEMBERIAN KOMPRES JAHE TERHADAP INTENSITAS NYERI GOUT ARTRITIS PADA LANSIA DI PSTW BUDI SEJAHTERA KALIMANTAN SELATAN - Putri, Senna Qobita Dwi; Rahmayanti, Devi; Diani, Noor (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
Gout artritis is a inflammatory disease where the impact caused form in the of pain. Based ofinformation from the Riskesdas in 2013, south Kalimantan Ranks seventh gout arthritissufferers 9.5%. the purpose of this study is to know the effect of ginger compress on theintensity of gout arthritis pain in elderly in PSTW Budi Sejahtera South Kalimantan. Thisresearch is an Quasy Eksperimental two goup pretest-postest The study was divided intotreatment group of ginger compress and control group of warm compress. The samplingtechnique using probability sampling and sample 32 the number of older people. Theinstruments used were in the form of ginger compress, warm compress, and observationalnumeric rating scale. The results showed is a effect of ginger compress (P-value = 0,00), soit could be concluded that H0 was rejected, where there is effect of ginger compress on theintensity of gout arthritis pain in elderly in PSTW Budi Sejahtera South Kalimantan.